Inhaled therapies in patients with moderate COPD in clinical practice: current thinking - Ariel, Amnon; Altraja, Alan; Belevskiy, Andrey; Boros, Piotr W; Danila, Edvardas; Fležar, Matjaz; Koblizek, Vladimir; Fridlender, Zvi G; Kostov, Kosta; Krams, Alvils; Milenkovic, Branislava; Somfay, Attila; et al. (International journal of chronic obstructive pulmonary disease, 2018)
COPD is a complex, heterogeneous condition. Even in the early clinical stages, COPD carries a significant burden, with breathlessness frequently leading to a reduction in exercise capacity and changes that correlate with long-term patient outcomes and mortality. Implementation of an effective management strategy is required to reduce symptoms, preserve lung function, quality of life, and exercise capacity, and prevent exacerbations. However, current clinical practice frequently differs from published guidelines on the management of COPD. This review focuses on the current scientific evidence and expert opinion on the management of moderate COPD: the symptoms arising from moderate airflow obstruction and the burden these symptoms impose, how physical activity can improve disease outcomes, the benefits of dual bronchodilation in COPD, and the limited evidence for the benefits of inhaled corticosteroids in this disease. We emphasize the importance of maximizing bronchodilation in COPD with inhaled dual-bronchodilator treatment, enhancing patient-related outcomes, and enabling the withdrawal of inhaled corticosteroids in COPD in well-defined patient groups.
Keywords: Exercise Tolerance; Lung; Muscarinic Antagonists; dual bronchodilation; Quality of Life; výsledek terapie; LABA; kvalita života; Health Status; lidé; zdravotní stav; Recovery of Function; Bronchodilator Agents; Pulmonary Disease, Chronic Obstructive; anticholinergic; inhaled corticosteroid; Treatment Outcome; Adrenal Cortex Hormones; hormony kůry nadledvin; antagonisté muskarinových receptorů; stupeň závažnosti nemoci; obnova funkce; Risk Factors; chronická obstrukční plicní nemoc; progrese nemoci; agonisté beta-2-adrenergních receptorů; Adrenergic beta-2 Receptor Agonists; Disease Progression; rizikové faktory; plíce; tolerance zátěže; tiotropium; aplikace inhalační; Severity of Illness Index; Administration, Inhalation; bronchodilatancia; LAMA; Humans